"Dancing on the ceiling" : young Black entrepreneurs leveraging capitals across sub-fields in Johannesburg tourism. (2nd September 2021) - Cooper, Adam
ABSTRACT: Rather than framing the South African youth unemployment debate in deficit terms, highlighting a lack of skills, educational and economic growth, this study focuses on creative practices and aspirations of Black youth in the Johannesburg tour- ism industry. This group's activities included tours of former migrant hostels, derelict buildings and township bicycle tours. These young entrepreneurs were placed at a fault line between township and mainstream economies, hustling capitals from various spaces to generate an income. Life histories of four young male entrepreneurs are described in detail. Their knowledge of and access to the inner-city and townships was desirable to certain tourists, creating a demand for "raw" or "authentic" experiences in informal settings. However, their origins in marginalised spaces, the operations of the main- stream capitalist economy and limited financial capital produced structural barriers to their rising too high. Johannesburg therefore mediated the acquisition and use of different forms of capital that Black youth tried to accumulate and use for income generation opportunities in the tourism sector. The inner-city and townships formed both a ceiling and a "dance floor, " enabling them to create innovative livelihoods, but these sites simultaneously and paradoxically pre- scribed limits to their upward social mobility.